Analisis Penerapan Metode Activity Based Costing Dan Metode Target Costing Dalam Perhitungan Laba Perusahan - Ni Luh Laksmi Dewi Ulandari; I Gede Agus Pertama Yudantara; I Gd Nandra Hary Wiguna (Vokasi : Jurnal Riset Akuntansi, 2026)
This study aims to analyze the application of Activity Based Costing (ABC) and Target Costing methods in profit calculation at PT Mitra Keluarga Karyasehat Tbk during the period 2019–2024. The cost calculation method currently used by the company is a conventional costing method, which has the potential to cause cost distortion because overhead costs are not allocated based on cost-driving activities. This research employs a descriptive quantitative approach using secondary data obtained from the company’s financial statements. Data analysis techniques were conducted by comparing profit calculations using the conventional method, Activity Based Costing, and Target Costing. The results of the study indicate that the Activity Based Costing method produces more accurate cost calculations because costs are allocated based on activities that consume resources. This method is able to identify activities that absorb the highest costs, thereby providing more relevant information for management in controlling operational costs. Meanwhile, the application of Target Costing shows that there are opportunities for cost efficiency through better cost control in order to achieve the targeted profit without reducing the quality of healthcare services. Therefore, the simultaneous application of Activity Based Costing and Target Costing can assist PT Mitra Keluarga Karyasehat Tbk in improving the accuracy of profit calculation and supporting more effective managerial decision-making.